The idea of the university in Australia in the 1990s. - Sinclair-Jones, Janet A. (Curtin University, 1996)
Over the past ten years Australian higher education has undergone a transformation from a binary structure, marked by a division of 'traditional universities' and colleges of advanced education, to a uniform university structure. This transformation was first proposed in 1987 by the Hon. John Dawkins, Minister for Employment, Education and Training in the Hawke Labor Government. The proposals appeared in the form of a 'Green' policy discussion paper which drew substantial amounts of criticism from the academy, but nonetheless were swiftly transformed into policy as a 'White' paper or policy statement. Since that time, Australian higher education institutions have been subject to a series of changes that have fundamentally changed the patterns of tertiary education provision established over the previous forty years. They have experienced a re-allocation of research funds which has eroded the established advantage of the traditional universities; they have been obliged to accept amalgamations; and, student numbers have expanded at a rate and to a proportion never previously imagined. All of this has been achieved under the banner of improving Australia's place in the highly competitive international economy. The champions of a restructured higher education sector have argued that this competitiveness is greatly dependent upon Australia's ability to improve the scientific and technical base of its human capital: higher education must move towards a more efficient and effective provision of education which will meet the needs of the market.The transformation of higher education has been achieved without the unanimous blessing of the academy. Many of the most strident critics of what have come to be known as the Dawkins Reforms are academics who have expressed dismay at these changes. In particular there has been as strongly argued case that the reforms, with their emphasis on science and technology, mark the end of liberal education in Australia. Australian higher education is now, they declare, the site of mass education based upon a new instrumentalism in which the liberal arts have no significant place.This dissertation takes such criticisms as its focus. In particular it attempts to show that the critique founded upon a defence of the inherent role of liberal education in the Australian university sector has been misguided. Furthermore, the dissertation argues that because so much of the attack on the restructuring policy took this form there was little place for a substantial critical appraisal of the validity of restructuring based upon an imperative of the market.The idea of the university in Australia as one fundamentally defined by liberal education is examined at two levels. First, it is argued that the notion of liberal education used to defend the university against new instrumentalism is an idealised notion which both ignores the historical construction of such an idea at a time when liberalism itself was undergoing transformation, and, wrongly assumes the absence of instrumentalism, within it. Second, the history of the establishment of the university in Australia is reviewed to show that whilst the founders of the universities often had sympathies for the liberal arts, from the outset Australian universities were consistently conditioned by the drive for instrumental education.Higher education policies in the post-WWII era are given particular attention in order to show that mass higher education is no new phenomenon, but the continuation of the drive towards expanded education provision. Just as with the expansion of schooling to mass schooling, a greatly expanded higher education sector has been necessary to fulfil the continued demands of the social democratic consensus. The thesis concludes with the argument that the critique of higher education reforms has been hobbled by the absence of a critical sociology of education which could place the restructuring of Australian higher education in the context of the transformation of social to market democracy.